Menahem Kahana. Sifre Zuta Deuteronomy: Citations from a New Tannaitic Midrash. Jerusalem: Magnes Press, 2002. 476 pp. (Hebrew) - Kulp, Joshua (AJS review, 2003)
In 1989, after the fall of the Iron Curtain in the former Soviet Union, Menahem Kahana of the Hebrew University in Jerusalem was the first Israeli scholar to search the St. Petersburg and Moscow libraries for manuscripts of rabbinic texts, and especially for lost halakhic midrashim. During his second visit, Kahana noticed that in a commentary on Deuteronomy written by a tenth-century Karaite sage named Yeshua ben Yehuda from Jerusalem, there were derashot to Deuteronomy that are unknown from any other rabbinic source. At first, he tentatively assumed that these quotations were from lost sections of the Mekhilta on Deuteronomy. However, the more Kahana culled quotations from the 30 (!) manuscripts of Yeshua's commentary, the more he realized that the terminological differences between these derashot and Mekhilta on Deuteronomy, coupled with the absence of these sources from Midrash Hagadol, which was familiar with Mekhilta on Deuteronomy, precluded such identification. In 1993, Kahana lectured on these derashot and identified them as belonging to a third tannaitic midrash on Deuteronomy (Sifre on Deuteronomy being the first), which he entitled Sifre Zuta Deuteronomy (SZD) based on its similarities to the already known Sifre Zuta Numbers (SZN).